2015
DOI: 10.1136/oemed-2014-102428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of summer outdoor temperatures on work-related injuries in Quebec (Canada)

Abstract: This study is the first to quantify the association between work-related injury compensations and exposure to summer temperatures according to physical demands of the occupation and this warrants further investigations. In the context of global warming, results can be used to estimate future impacts of summer outdoor temperatures on workers, as well as to plan preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
61
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 27 publications
14
61
1
2
Order By: Relevance
“…Evidence suggests that the exposure to high environmental temperatures not only affects workers' capability to undertake physical activities without harm, especially in subjects with pre-existing illnesses [2,5,[18][19][20][21][22][23][24] but high temperatures would significantly hamper cognition and concentration of the workers, reducing vigilance and increasing fatigue: as a consequence, working during warm weather would also ultimately increase the risk of mistakes, accidents and occupational injuries (OIs) [14,[25][26][27][28][29]. The risk of heat-related health effects appears to be significantly increased in outdoors workers such as agricultural workers (AWs), for several reasons [5,30,31].…”
Section: Materials and Methods Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that the exposure to high environmental temperatures not only affects workers' capability to undertake physical activities without harm, especially in subjects with pre-existing illnesses [2,5,[18][19][20][21][22][23][24] but high temperatures would significantly hamper cognition and concentration of the workers, reducing vigilance and increasing fatigue: as a consequence, working during warm weather would also ultimately increase the risk of mistakes, accidents and occupational injuries (OIs) [14,[25][26][27][28][29]. The risk of heat-related health effects appears to be significantly increased in outdoors workers such as agricultural workers (AWs), for several reasons [5,30,31].…”
Section: Materials and Methods Settingsmentioning
confidence: 99%
“…These inconsistencies with available literature may be explained recalling some specificities of the agricultural activities in the Subalpine regions. First of all, most of agricultural works follow crop growth [5,19,44]. Even though certain agricultural activities may benefit from a short delay when weather conditions are particularly uncomfortable, the majority of agricultural activities have to be performed in a restricted time window, following the timetable imposed by crops and cultivations, not allowing the AWs to usually spare holidays and weekend.…”
Section: Ijomeh 2018;31(3) 323mentioning
confidence: 99%
“…Younger people may be engaged in physically demanding or outdoor work, for example in agriculture and construction sector, making them more vulnerable to high temperatures [49]. The previous studies also reported that high temperature was associated with a higher risk of work-related injuries [50,51] although the health impact of high temperature has not been fully studied in occupational settings.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming widely recognized that occupational health and safety (OHS) and productivity can be compromised in hot conditions, with several studies reporting on the phenomenon in Canada [1][2][3], the United States of America [4,5], Europe [6,7], Asia [8,9] and Australia [10][11][12][13][14][15][16]. As global temperatures rise and extreme temperatures become more common, prevention measures in workplaces will be essential.…”
Section: Introductionmentioning
confidence: 99%